Bosadi on Justice: An African Liberationist Reading of Psalm 72 and the Song “Uhuru” in Addressing Poverty in Africa - Mtshiselwa, Ndikho (Old Testament Essays, 2025)
Old Testament scholars have proposed various interpretations of Psalm 72, which range from the psalm being a coronation hymn that addresses issues of leadership, to the text addressing geo-political relations, to a psalm offering a reflection on poverty in various contexts in ancient Israel. However, enthused by Bosadi an African liberationist reader of the text poses the main question: When viewed as part of the biblical “protest literature,” would Psalm 72 offer liberating possibilities for the poor people in its worlds of production and literary development as well as the South African context if read with an African liberationist lens that is foregrounded in the Bosadi theoretical framework? First the essay discusses some aspects of the Bosadi theoretical framework and the African liberationist paradigm that may provide a window to the discourse of poverty in South Africa and the psalm. Seconds, the article employs a popular song, “Uhuru” as a hermeneutical tool within the Bosadi theoretical framework and African liberationist paradigm to offer a reflection on poverty in South Africa. Third, set within the latter theoretical framework and paradigm as well as in light of the depiction of poverty in the song, “Uhuru,” the essay explores poverty in the grammatical and stylistic features of Psalm 72. In the end, while celebrating Masenya (ngwan’a Mphahlele)’s love for Jesus, the Lord and Saviour, in her Christian faith and scholarship, the article teases out problematic elements of the psalm (Hebrew Bible) and liberating features for humanity trapped in poverty.